2019
DOI: 10.1111/bdi.12857
|View full text |Cite
|
Sign up to set email alerts
|

Predominant polarity and hippocampal subfield volumes in Bipolar disorders

Abstract: Objectives Predominant polarity (PP) is a proposed course specifier for bipolar disorders (BD) based on patient lifetime mood episodes. Hippocampal subfield volumetric changes have been proposed as a neurobiological marker for BD and could be influenced by mood episodes. Our study aimed to test the hypothesis that patients with BD differ in hippocampal subfield volumes according to their PP. Methods We assessed 172 outpatients, diagnosed with BD according to DSM‐IV‐TR criteria, and 150 healthy control (HC) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 50 publications
2
18
1
1
Order By: Relevance
“…Predominant polarity (PP) is a longitudinal course specifier based on the observation that subgroups of patients with BD present with a lifetime tendency towards one affective pole (either mania or depression), and it has been an important concept in gaining a longitudinal understanding of illness course. A recent study by our group found hippocampal subfield volume differences between patients with manic or depressive PP 4 . These findings offered biological support for PP as a clinical specifier and strengthened the concept that research models in BD should take into account the longitudinal course of the illness when identifying recurrence.…”
Section: Figuresupporting
confidence: 61%
“…Predominant polarity (PP) is a longitudinal course specifier based on the observation that subgroups of patients with BD present with a lifetime tendency towards one affective pole (either mania or depression), and it has been an important concept in gaining a longitudinal understanding of illness course. A recent study by our group found hippocampal subfield volume differences between patients with manic or depressive PP 4 . These findings offered biological support for PP as a clinical specifier and strengthened the concept that research models in BD should take into account the longitudinal course of the illness when identifying recurrence.…”
Section: Figuresupporting
confidence: 61%
“…Abnormalities have been primarily reported in subcortical nuclei and prefrontal-temporal-limbic circuits (33)(34)(35). Interestingly, the same brain networks have been highlighted as specific targets of stress-induced mood symptomatology (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…52 This could underpin a genetic heterogeneity including a partial overlap with other psychosis 53 and neurobiological underpinnings of predominant polarity which are still under study. 36,54 This study has potential limitations. First, socio-cultural factors that could complicate the detection of acute affective episodes (eg, holidays) were not considered, translating into a recollection bias.…”
Section: Discussionmentioning
confidence: 95%
“…The etiology of seasonal fluctuations in BD is still unclear, but biorhythm alterations, such as in levels of energy, sleep quality/quantity, and duration among others, are structural characteristics of an acute mood episode, 8 possibly accounting for a part of the clinical heterogeneity witnessed both in euphoric states and even more in depression 52 . This could underpin a genetic heterogeneity including a partial overlap with other psychosis 53 and neurobiological underpinnings of predominant polarity which are still under study 36,54 …”
Section: Discussionmentioning
confidence: 99%